Women in the dark female photographers in the US, 1850-1900 - Manthorne, Katherine 1952- (Schiffer Publishing, 2020)
"Recover the stories of long-overlooked American women who, at a time when women rarely worked outside the home, became commercial photographers and shaped the new, challenging medium. Covering two generations of photographers ranging from New York City to California's mining districts, this study goes beyond a broad survey and explores individual careers through primary sources and new materials. Profiles of the photographers animate their careers by exploring how they began, the details of running their own studios, and their visual output. The featured photos vary in form--daguerreotype, tintype, carte de visite, and more--and subject, including Civil War portraits, postmortem photography, and landscape photography. This welcome resource fills in gaps in photographic, American, and women's history and convincingly lays out the parallels between the growth of photography as an available medium and the late-19th-century women's movement."--
Keywords: Geschichte 1850-1900; Frauenbewegung; Fotografin; Porträtfotografie; USA; Women photographers / United States / Biography; Women photographers / United States / 19th century; Photography / History / 19th century; Photography; Women photographers; United States; 1800-1899; History; Biographies